2017
DOI: 10.3390/ma10020098
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Properties of Open-Cell Al Hybrid Foams at Different Temperatures

Abstract: Hybrid Ni/Al foams were fabricated by depositing electroless Ni–P (EN) coatings on open-cell Al foam substrate to obtain enhanced mechanical properties. The microstructure, chemical components and phases of the hybrid foams were observed and analyzed by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD), respectively. The mechanical properties of the foams were studied by compressive tests at different temperatures. The experiment results show that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It can be seen that the stress oscillations are significant at elevated temperatures, especially at 200 • C, which is believed that attributed to the brittle deformation behavior of the foams [1,2]. In addition, the compressive strength and energy absorption capacity of the composite foams decrease with the increase of temperature and this downward trend of the composite foams is similar to that of the as-received Al foams due to the softening effect of elevated temperature on the Al strut [23]. As shown in Figure 8b, the temperature also induces a decrement in the energy absorption capacity.…”
Section: Element and Phase Composition Of The Peo Coatingmentioning
confidence: 95%
“…It can be seen that the stress oscillations are significant at elevated temperatures, especially at 200 • C, which is believed that attributed to the brittle deformation behavior of the foams [1,2]. In addition, the compressive strength and energy absorption capacity of the composite foams decrease with the increase of temperature and this downward trend of the composite foams is similar to that of the as-received Al foams due to the softening effect of elevated temperature on the Al strut [23]. As shown in Figure 8b, the temperature also induces a decrement in the energy absorption capacity.…”
Section: Element and Phase Composition Of The Peo Coatingmentioning
confidence: 95%
“…Recently, surface treatment has been observed to be a more convenient method for enhancing the energy absorption of aluminium foams. Anodising [7][8][9][10] and metal deposition [11][12][13][14][15] are commonly used for surface treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition of metal coatings (e.g. Ni and Cu) is another effective method for enhancing the energy absorption capability [11][12][13][14][15]. At least a onefold increase in energy absorption was observed in aluminium foam after Ni deposition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid foams belong to the group of composite foams and are characterized by a combination of different materials. Typical hybrid foams are copper (Cu)/Al hybrid foams [6][7][8] and Ni/polyurethane (PU) hybrid foams [9]. Ni/Al hybrid foams are made from an Al base foam.…”
Section: Introductionmentioning
confidence: 99%
“…A lower elastic modulus promotes bending and buckling of struts resulting in a reduced compressive strength. Liu et al concluded that interface debonding is a main failure mechanism during compression of hybrid foams at room temperature and at 200 • C [9]. In order to address the weak point interface, it is important to understand the failure mechanism in view of the interface morphology.…”
Section: Introductionmentioning
confidence: 99%